Remote parole oral hearings: More efficient, but at what cost? - Peplow, David (Criminology & criminal justice, 2025)
The Parole Board (PB) is responsible for deciding whether some prisoners are safe to be released into the community. COVID-19 accelerated the PB’s move towards using remote oral hearings. Little is known about how this shift towards remote working has impacted the work of the PB and prisoners. In this article, we present the findings from a study that sought to understand the differences between remote and in-person hearings. Through analysis of interviews with 15 PB panel members we identify benefits and disbenefits of remote hearings. We suggest that in-person hearings are perceived to be better and that remote hearings pose challenges to participation, especially for certain prisoners. However, we also find that remote hearings bring benefits, such as greater efficiency for the organisation. We conclude that the Board needs to reconcile the tension between the efficiency afforded by remote working and the risks to justice that exist in this context.